Die Beschreibung der Nilflut in der Nilkammer von Edfu - Baumann, Stefan (Zeitschrift für ägyptische Sprache und Altertumskunde, 2012)
Inside the so-called Nile Chamber of the Horus Temple in Edfu a relief is engraved, displaying six gods that are related to the inundation of the Nile.